2020
DOI: 10.1186/s13229-020-00352-3
|View full text |Cite
|
Sign up to set email alerts
|

Defining clusters of young autistic and typically developing children based on loudness-dependent auditory electrophysiological responses

Abstract: Background: Autistic individuals exhibit atypical patterns of sensory processing that are known to be related to quality of life, but which are also highly heterogeneous. Previous investigations of this heterogeneity have ordinarily used questionnaires and have rarely investigated sensory processing in typical development (TD) alongside autism spectrum development (ASD). Methods: The present study used hierarchical clustering in a large sample to identify subgroups of young autistic and typically developing ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
2
23
1
Order By: Relevance
“…While prior studies such as those of Dwyer et al (2020) and Schwartz et al (2020b) have found relationships between auditory ERPs and sensory questionnaire scores, both Dwyer et al (2020) and Schwartz et al (2020b) presented auditory stimuli while participants watched quiet or silent videos of personal interest. Thus, it seems possible that neurophysiological responses to sensory stimuli might track better with the daily sensory experiences of autistic individuals if recorded in an experimental paradigm with multiple stimuli competing for attention, more closely resembling the complex real-world environments on which sensory questionnaire reporting may be based.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…While prior studies such as those of Dwyer et al (2020) and Schwartz et al (2020b) have found relationships between auditory ERPs and sensory questionnaire scores, both Dwyer et al (2020) and Schwartz et al (2020b) presented auditory stimuli while participants watched quiet or silent videos of personal interest. Thus, it seems possible that neurophysiological responses to sensory stimuli might track better with the daily sensory experiences of autistic individuals if recorded in an experimental paradigm with multiple stimuli competing for attention, more closely resembling the complex real-world environments on which sensory questionnaire reporting may be based.…”
Section: Discussionmentioning
confidence: 96%
“…Some prior studies have also examined, in ASD, convergence between questionnaire reports of sensory processing and ERP/ERF responses to auditory stimuli. For example, larger early neural responses to sounds could be related to reports of auditory distractibility or sensory sensitivity ( Karhson and Golob, 2016 ; Dwyer et al, 2020 ). Prior research has also explored associations between questionnaire-reported sensory behaviors and auditory mismatch/P3 responses ( Ludlow et al, 2014 ; Chien et al, 2017 ) as well as ERP indices of auditory habituation ( Hudac et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG data were collected at Time 1 in the APP, when participants were aged 2 through 4 years. The EEG task and processing procedures employed in the present study have been described in greater detail elsewhere (De Meo-Monteil et al, 2019;Dwyer et al, 2020bDwyer et al, , 2021. Briefly, while participants were seated in a caregiver's lap watching a video of their choice, approximately ~ 1200 50 ms complex tones (combining multiple frequencies) of four intensities (50, 60, 70, and 80 dB SPL) were presented binaurally using headphones at a random interstimulus interval of 1-2 s. EEG was sampled at 1000 Hz using a 61-channel electrode cap (easycap.de).…”
Section: Eeg Task and Processingmentioning
confidence: 99%
“…For example, caregiver-report questionnaires have been criticized on the grounds that caregivers lack direct insight into the internal sensory experiences of autistic people and can therefore only report on external behaviours, which might be misleading (Grandin & Panek, 2014 ). This is concerning, as most studies describing sensory subgroups in autism have relied on caregiver-report questionnaires (see DeBoth & Reynolds, 2017 ), with exceptions including a study based on a self-report questionnaire (Elwin et al, 2017 ) and one based primarily on auditory event-related potentials (ERPs; Dwyer et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%